Pelatihan Manajerial untuk Meningkatkan Kinerja Organisasi - I Gede Putu Kawiana (UNHI Press, 2022)
In its development until the current COVID-19 pandemic, (end of 2021) LPD are still faced with performance problems. LPD that are not good and that have gone bankrupt are mostly due to internal LPD problems. The internal problems that can be identified include the competence of human resources (HR), the implementation of good corporate governance (GCG), and leadership. To fill these gaps, training for LPD administrators, improving their managerial abilities and their commitment to improving organizational performance. The objectives of this managerial training are; the strategy chosen effectively and effectively, performance, reviewing the situation and making various adjustments and corrections if there are deviations in the implementation of the strategy, always updating the formulated strategy to suit external developments, always reviewing strengths, threats, opportunities and existing ones, always exercising on activities so that we live more regularly.